2016
DOI: 10.3892/etm.2016.3783
|View full text |Cite
|
Sign up to set email alerts
|

Downregulated miR-486-5p acts as a tumor suppressor in esophageal squamous cell carcinoma

Abstract: Abstract. microRNAs (miRNAs/miRs) are crucial regulators of gene expression at the post-translational level through promoting mRNA degradation or the repression of translation of target genes. miRs have been confirmed to serve a dominant role in tumor biology. miR-486-5p has been ascertained to be involved in non-small-cell lung cancer, breast cancer and hepatocellular carcinoma; however, the expression and function of miR-486-5p in esophageal squamous cell carcinoma (ESCC) has yet to be elucidated. The presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 39 publications
2
34
0
Order By: Relevance
“…Emerging evidence has revealed that miR-486-5p acts as an oncogene or tumor suppressor in various cancers, including non-small cell lung cancer, prostate cancer, esophageal squamous cell carcinoma, and papillary thyroid carcinoma 12 , 28 30 . However, its biological role in CRC remains elusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence has revealed that miR-486-5p acts as an oncogene or tumor suppressor in various cancers, including non-small cell lung cancer, prostate cancer, esophageal squamous cell carcinoma, and papillary thyroid carcinoma 12 , 28 30 . However, its biological role in CRC remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging studies reported that miRNAs regulate approximate 60% protein-coding genes that are linked with several biological processes, including cell proliferation, apoptosis, invasion, chemosensitivity, and so on 9 – 11 . Recently, increasing evidence demonstrated that miR-486-5p acts as a tumor inducer or suppressor in multiple human malignancies 12 14 . Besides, The Cancer Genome Atlas (TCGA) database illustrated that miR-486-5p is one of the most downregulated miRNAs in CRC.…”
Section: Introductionmentioning
confidence: 99%
“…Later, the researchers continued to find the corresponding miRNA from fruit flies, human beings, plants and other eukaryotes (9). Growing evidence has suggested that they are mediators of the genetic expression, modification, transcription as well as translation (9).…”
Section: Discussionmentioning
confidence: 99%
“…Later, the researchers continued to find the corresponding miRNA from fruit flies, human beings, plants and other eukaryotes (9). Growing evidence has suggested that they are mediators of the genetic expression, modification, transcription as well as translation (9). It was found that the miRNA polymorphism, abnormal miRNA expression, as well as receptors affecting gene expression on drug uptake, metabolism and distribution pathways, as well as targeting clinical function may significantly affect the therapeutic effects of antitumor drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation